Is borderline personality disorder really an emotion dysregulation disorder and, if so, how? A comprehensive experimental paradigm. Issue 12 (17th November 2020) - Fitzpatrick, Skye; Varma, Sonya; Kuo, Janice R.
Abstract: Background: Leading theories suggest that borderline personality disorder (BPD) is an emotion dysregulation disorder involving lower basal vagal tone, higher baseline emotion, heightened emotional reactivity, delayed emotional recovery, and emotion regulation deficits. However, the literature to date lacks a unifying paradigm that tests all of the main emotion dysregulation components and comprehensively examines whether BPD is an emotion dysregulation disorder and, if so, in what ways. This study addresses the empirical gaps with a unified paradigm that assessed whether BPD is characterized by five leading emotion dysregulation components compared to generalized anxiety disorder (GAD) and healthy control (HC) groups. Methods: Emotion was assessed across self-report, sympathetic, and parasympathetic indices. Participants with BPD, GAD, and HCs ( N = 120) first underwent baseline periods assessing basal vagal tone and baseline emotional intensity, followed by rejection-themed stressors assessing emotional reactivity . Participants then either reacted normally to assess emotional recovery or attempted to decrease emotion using mindfulness or distraction to assess emotion regulation implementation deficits . Results: Individuals with BPD and GAD exhibited higher self-reported and sympathetic baseline emotion compared to HCs. The BPD group also exhibited self-reported emotion regulation deficits using distraction only compared to the GAD group. Conclusions: There is minimal support for several emotion dysregulation components in BPD, and some components that are present appear to be pervasive across high emotion dysregulation groups rather than specific to BPD. However, BPD may be characterized by problems disengaging from emotion using distraction.